Konstruktivisme Model Pembelajaran Kognitif Moral Melalui Aplikasi “Dimo” Untuk Meningkatkan Kemampuan Moral Decision Siswa Sekolah Dasar - Faiz, Aiman; Fadly, Aris (Jurnal Konseling dan Pendidikan, 2024)
To offset the concerns that arise due to changes in human behavior caused by rapid and unstoppable technological advances, the field of education needs to provide various reinforcements, one of which is through the learning process. Research to see the improvement of elementary school students' moral decisions through the cognitive moral development model assisted by the "Dimo" application on an Android smartphone. This study uses a pre-experimental design One - Group Pretest-Posttest. The informants of this study were 31 6th grade students at SDN 4 Kenanga, Cirebon Regency. This study resulted in differences in pre and post tests tested on 31 students. The pre-test of the majority of students was in the pre-conventional stage 2 category with 95 choices with a percentage of 61.2%. After treatment and presentation of the "Dimo" application media as a learning medium, 75 students' answers were in the conventional stage 2 with a percentage of 48.3%. These results indicate that with the help of the "Dimo" moral dilemma application media, students' moral considerations and moral decision making can improve. This means that the use of application media for students can provide a complex understanding of the problems of moral dilemmas presented because they are more concrete in audio-visual form. This is also in accordance with the characteristics of the current generation of students who are closely related to technology. This study provides recommendations that with active and varied models, students can better understand the context of the learning presented.